Computational analysis on missense mutation of ornithine transcarbamylase (OTCase) enzyme / Ernie Zuraida Ali - Ali, Ernie Zuraida (2020)
Missense mutations occur close to the binding pocket of ornithine transcarbamylase (OTCase) enzyme associated with a severe form of ornithine transcarbamylase deficiency (OTCD), an X-linked disorder. These mutations affect the functions of OTCase enzyme in the body that can lead to acute clinical symptoms. Early diagnosis and intervention is crucial for effective decision on managing patients and reducing mortality rate. However, the current diagnosis and biochemical analyses being used are still time consuming, labour intensive and costly. Therefore, in this work, three (3) stages of computational approaches (mutation prediction servers, molecular docking, molecular dynamics simulations) are explored and implemented to predict the severity of the missense mutations in OTCD. The findings are based on two novels, Q171H and N199H, and 30 other known missense mutations located in the OTCase ligand binding pocket. The novel mutations were obtained from the nucleotide sequencing results from two OTCD Malaysian patients, while the other 30 known mutations were collected from HGMD and 1000G browser databases. The consensus prediction of five mutation prediction servers concluded all 32 mutations are disease-causing. Further study using docking of PALO ligand, an analog of N-phosphonacetyl-Lornithine resulted in binding of the ligand to the mutant OTCase structures with slightly differently conformation when compared to the wild type structure. In the final stage, MD simulations of the mutant complexes (Q171H-PALO, N199H-PALO, R92P-PALO and H168R-PALO) confirmed the conformational instability due to the disruption of intermolecular interactions between PALO and OTCase. The missense mutations disrupted hydrogen bond interactions with the neighbouring residues (S267, M268, D263, C303, R330 and E326), including residues involved in the catalytic mechanism (C303, D263 and R330). In addition, the role of SMG loop as a second ligand recognition site was observed during the simulations. Application of computational approaches successfully revealed the mutations potentially disturb catalytic efficiency contributing to the occurrence of various OTCD symptoms. In conclusion, computational approaches can potentially be used as preliminary screening and rapid diagnosis for new mutation as it can provide the fast result, save time and cost.